Examining downdraft gasifiers at various equivalent ratios using deoiled cashew nut shells as gasification feedstock - H.Y. Shrirame; A.G. Mohod; Y.P. Khandetod; K.G. Dhande (Energy Nexus)
Cashew nut shell waste generated by cashew processing enterprises is disposed of in open land or burned in a semi-open pit, causing environmental issues. The current study examines gasification as an alternate method of reclaiming energy from cashew nut shell waste. This paper discusses an experimental investigation of downdraft gasifier that was conducted for various Equivalence Ratios (ER). The five different ER (0.25–0.45) were selected to investigate a 12.79 kW downdraft gasifier performance using deoiled cashew nut shell (DCNS) as feedstock. The fuel consumption rate (FCR), specific gasification rate (SGR), gas production rate (GPR) and power rating (PR) were observed in the range of 3.17–4.00 kg h-1, 8.82–11.11 kg m-2 h-1, 4.49–7.93 m3 h-1 and 8.69–10.99 kW respectively with the increase in ER (0.25–0.45). Whereas gasifier operating time and tar content were decreased with the increase in ER. The maximum combustion efficiency, cold gasification efficiency and hot gasification efficiency of downdraft gasifier were found to be 51.87 %, 39.85 % and 42.07 % respectively at 0.35 ER. The higher heating value (HHV) of producer gas under the optimum operating conditions i.e. at 0.35 ER is about 4.79 MJ Nm-3.